2021
DOI: 10.1088/1361-6463/ac18f0
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide@cobalt oxide core–shell nanostructure, as an efficient binder-free anode for lithium-ion batteries

Abstract: Here, cobalt oxide nanostructures synthesized on vertically aligned copper oxide nanowires (NWs) have been investigated as a possible anode material for Lithium-ion batteries (LIBs). Copper oxide NWs were formed by thermal oxidation of electrochemically deposited copper on the stainless steel mesh substrate. The process used allows the formation of highly dense copper oxide NWs with excellent adhesion to the conductive current collector substrate. A simple hydrothermal method was implemented for the deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…[7][8][9][10][11][12] In this regard, a great deal of research has been focused on creating batteries with increased specic energy, capacity, and safety. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] It has been proven that LIBs with silicon-based anodes are capable of supporting these benets if properly engineered, and therefore, aer an enormous amount of investment and research in this eld, they have now found their way into commercial LIBs. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Silicon-based anodes have been successfully employed in LIBs by nding solutions for their enormous volume change, unstable solid electrolyte interface (SEI) layer, and low electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] In this regard, a great deal of research has been focused on creating batteries with increased specic energy, capacity, and safety. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] It has been proven that LIBs with silicon-based anodes are capable of supporting these benets if properly engineered, and therefore, aer an enormous amount of investment and research in this eld, they have now found their way into commercial LIBs. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Silicon-based anodes have been successfully employed in LIBs by nding solutions for their enormous volume change, unstable solid electrolyte interface (SEI) layer, and low electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…7–12 In this regard, a great deal of research has been focused on creating batteries with increased specific energy, capacity, and safety. 13–30…”
Section: Introductionmentioning
confidence: 99%